Mono‐ and Bis‐Alkylated Lumazine Sensitizers: Synthetic, Molecular Orbital Theory, Nucleophilic Index and Photochemical Studies. (25th August 2020) - Sosa, María José; Urrutia, María Noel; Schilardi, Patricia L.; Quindt, Matías I.; Bonesi, Sergio M.; Denburg, Dobrushe; Vignoni, Mariana; Greer, Alexander; Greer, Edyta M.; Thomas, Andrés H.
Abstract: Mono ‐ and bis ‐decylated lumazines have been synthesized and characterized. Namely, mono ‐decyl chain [1‐decylpteridine‐2, 4(1, 3 H )‐dione] 6a and bis ‐decyl chain [1, 3‐didecylpteridine‐2, 4(1, 3 H )‐dione] 7a conjugates were synthesized by nucleophilic substitution (S N 2) reactions of lumazine with 1‐iododecane in N, N ‐dimethylformamide (DMF) solvent. Decyl chain coupling occurred at the N 1 site and then the N 3 site in a sequential manner, without DMF condensation. Molecular orbital (MO) calculations show a p ‐orbital at N 1 but not N 3, which along with a nucleophilicity parameter ( N ) analysis predict alkylation at N 1 in lumazine. Only after the alkylation at N 1 in 6a, does a p ‐orbital on N 3 emerge thereby reacting with a second equivalent of 1‐iododecane to reach the dialkylated product 7a . Data from NMR ( 1 H, 13 C, HSQC, HMBC), HPLC, TLC, UV‐vis, fluorescence and density functional theory (DFT) provide evidence for the existence of mono ‐decyl chain 6a and bis ‐decyl chain 7a . These results differ to pterin O ‐alkylations (kinetic control), where N ‐alkylation of lumazine is preferred and then to dialkylation (thermodynamic control), with an avoidance of DMF solvent condensation. These findings add to the list of alkylation strategies for increasing sensitizer lipophilicity for use in photodynamic therapy. Abstract : Mono ‐ and bis ‐decylated lumazines have been synthesized and photochemically characterized. The decyl chain coupling is selective for the N 1 site and then couples a second equivalent of the decyl chain to reach the bis ‐alkylated lumazine. The reactivity is rationalized by molecular orbital theory calculations along with Mayr's nucleophilicity parameters. Notably, N ‐alkylation of lumazine is preferred (thermodynamic control), which is in contrast to the preference of O ‐alkylation in pterins (kinetic control).